Physicochemical Characteristics, Antioxidant Activity and Sensory of Cookies Based on Mocaf, Purple Yam, and Cinnamon Flour - Satar, Ibdal; Emilia, Defita Fajar (Universitas Airlangga, 2023)
In general, cookies are made by using wheat flour with high gluten content, consequently it may cause negative impact on health. So far, cookies also have not the characteristics as functional food that is beneficial for health. Based on these issues, wheat flour is needed to substitute with alternative materials in order to reduce the gluten and increase the functional characteristic of cookies. Mocaf, purple yam flour and cinnamon powder can be used to provide cookies with low gluten and have the characteristic of functional food. The aims of this research are to characterize the physicochemical and organoleptic properties of cookies based Mocaf flour, purple yam flour and cinnamon powder. This work was used he completely randomized design (CRD) with the formulations applied F0(100:0:0), F1(75:24.5:0.5), F2(75:24:1), F3(75:23.5:1.5). F4(50:49.5:0.5), F5(50:49:1), F6(50:48.5:1.5), F7(25:74.5:0.5), F8(25:74:1), and F9(25:73.5:1.5) with 3 replications. Analysis of physicochemical properties of cookies consists of moisture, fat, total protein, ash, carbohydrates contents, texture, and antioxidant activity. The organoleptic properties were tested by 30 semi-trained panelists. The collected data were analyzed by one way ANOVA at significance level of 5% and followed by Duncan's test. These results show the contents of fat, protein, ash, carbohydrate, water, antioxidant activities and hardness were obtained in the range of 28.1-29.4%, 3.3-3.6%, 1.5-2.2%, 59.8-62.1%, 44.5-88.8 ppm and 13.8 - 38.3 N, respectively. Based on the organoleptic tests, F2 cookies was most preference than other formulations. The cookies produced believes have low gluten and food functional properties